Role of GraphDB in FinTech, Blockchain Ledgers - Kaleem, Hassan; Rukhsar, Sundas; Ahmad, Waqar; Haris, Hafiz Ali (UMT Artificial Intelligence Review, 2023)
GrpahDB stores data in nodes and edges, nodes represent entities and edges represents the relationship between entities. The role of GraphDB in the blockchain is described as blockchain uses blocks and these blocks are connected through hashcode to store the data. In cipher language, hash is the irreversible conversion of data which makes it impossible to decrypt. Blockchain also uses proof of work system, in which data is entered only if maximum people allows verifies it. And once anything entered into ledger, it cannot be altered or deleted. The paper has provided how hashing & indexing, query processing, transaction management, data management and data distribution is done for GraphDB into ledger, with previously done work and libraries to build and manage GraphDB blockchain.